Spectroelectrochemical characterisation of copper salen-based polymer modified electrode - Martins, Madga (2011)
Electrogenerated polymers based on copper salen-type complexes were characterised electrochemically and by in situ UV–vis and ex situ EPR spectroscopy. The films, poly[Cu(salen)] and poly[Cu(saltMe)], exhibit reversible oxidative electrochemical behaviour in a wide potential range (0.0–1.5 V). Different regimes for charge transport behaviour are accessed by manipulation of film thickness and experimental time scale: thin films (surface concentration, Γ < ca. 80 nmol cm−2) show thin-layer/surface behaviour in the scan rate range used (0.020–2.0 V s−1), whereas thicker polymers (Γ > ca. 90 nmol cm−2) exhibit a changeover from thin-layer to diffusion control regime at a critical scan rate that depends on polymer and film thickness: 0.15–0.20 V s−1 for poly[Cu(salen)], 90 < Γ < 130 nmol cm−2 and 0.20–0.30 V s−1 for poly[Cu(saltMe)], 170 < Γ < 230 nmol cm−2. UV–vis and EPR spectroscopies have allowed the characterisation of electronic states in the reduced and oxidised forms. The role of the copper atom during film oxidation was probed by combining UV–vis data with EPR on copolymers of the copper and nickel complexes. Data from both techniques are consistent and indicate that polymerisation and redox switching are associated with ligand-based processes. EPR of Ni-doped Cu polymers provided evidence for the non-involvement of the metal centre in polymer oxidation; like the analogous nickel polymers, copper polymers behave like delocalised π-system (‘conducting’) rather than discrete site (‘redox’) polymers.